Developments of 3D polycaprolactone/beta-tricalcium phosphate/collagen scaffolds for hard tissue engineering - İNAN, AHMET TALAT; MUTLU MİTİL, BİLÇEN; OKTAR, FAİK NÜZHET; KURT, MUSTAFA; EKREN, NAZMİ; GÜNDÜZ, OĞUZHAN (SPRINGER, 2019)
3D bioprinting provides an innovative strategy to fabricate a new composite scaffold material consisted in a porous and rough structure with using polycaprolactone (PCL), beta-tricalcium phosphate (beta-TCP), and collagen as a building block for tissue engineering. We investigated the optimization of the scaffold properties based on the beta-TCP concentration using 3D bioprinting method. Computer-aided drawing was applied in order to digitally design the scaffolds while instead of solid filaments, materials were prepared as a blend solution and controlled evaporation of the solvent during the bioprinting was enabled the proper solidification of the scaffolds, and they were successfully produced with well-defined porous structure. This work demonstrated the feasibility of complex PCL/beta-TCP/collagen scaffolds as an alternative in the 3D bioprinting engineering to the fabrication of porous scaffolds for tissue engineering.
Keywords: Biomaterials; Biomedical engineering; Additive manufacturing; Hard tissue scaffolds; NANOFIBROUS SCAFFOLD